MAHKAMAH KONSTITUSI : ANTARA NEGATIVE LEGISLATURE DAN POSITIVE LEGISLATURE, DILEMA ATAU DINAMIKA? - YADJITALA, MUHAMMAD ALGUFRAN (Ganec Swara, 2025)
The Constitutional Court (MK) is a state institution that has high authority in the field of constitutional law. In Indonesia, the Constitutional Court is regulated by Article 24C of the 1945 Constitution which outlines the Constitutional Court’s authority, including reviewing laws against the Constitution, deciding disputes over authority between state institutions, deciding on the dissolution of political parties, and deciding disputes over general election results. The approach used in the research is to conduct a review of the conceptual approach and legal literature by examining various expert doctrines and legal theories regarding the positive legislative Constitutional Court. In the analysis, the result is that the Constitutional Court is basically a negative legislature. But then in its progress, many of the Court’s decisions were positive legislative in nature. This is due to the main principle that the Constitutional Court must believe in, namely filling legal gaps if they occur due to the impact of reviewing laws. This shift, which initially only annulled norms, can now give birth to norms. This is seen as a step that does not violate the constitution because the judge’s job is to make discoveries if there is a legal vacuum.